Magneto-Radiative Nanofluid Flow over a Stretching Permeable Sheet with Heat Generation and Slip Boundary Effects: Homotopy Perturbation Method - Babulal Talukdar; Gopinath Mandal (Sustainable Chemical Engineering, 2025)
This study explores the nanofluid's flow and heat transfer over a stretching surface, considering the influence of a Darcy-Forchheimer porous medium and an external magnetic field. Moreover, thermal radiation effects, heat source/sink impacts, and second-order slip boundary conditions are incorporated into the problem. The nanofluid is developed by dispersing copper (Cu) or alumina (Al2O3) nanoparticles into a water (H2O) base fluid. Appropriate similarity transformations are applied to convert the controlling equations into ordinary differential equations. This study's novelty lies in the homotopy perturbation method (HPM) used to solve the resultant highly nonlinear coupled differential equations analytically. The effects of several relevant factors are thoroughly examined using graphs and tables for skin friction, temperature, velocity, and heat transfer rate. The findings demonstrate that raising the magnetic parameter significantly increases the skin friction coefficient while lowering the heat transmission rate. The results show that raising the volume percentage of copper and alumina nanoparticles enhances the skin friction coefficient. Nusselt numbers are found to reduce with thermal radiation and thermal slip parameters for both nanofluid flows. This investigation has applications in paper manufacturing, metal sheet cooling, and crystal growth. In high-temperature industrial applications, radiation heat transfer research is critical.